Mean yield pressure from the in-die Heckel analysis is a reliable plasticity parameter - Vreeman, Gerrit; Sun, Changquan Calvin (International journal of pharmaceutics: X, 2021)
Despite the ability to characterize the plasticity of powders in a material-sparing and expedited manner, the in-die Heckel analysis has been widely criticized for its sensitivity to several factors, such as particle elastic deformation, tooling size, lubrication, and speed. Using materials exhibiting a wide range of mechanical properties, we show that the in-die Py correlates strongly with three established plasticity parameters obtained from the out-of-die Heckel analysis, Kuentz-Leuenberger analysis, and macroindentation. Thus, the in-die Py is a reliable parameter for quantifying powder plasticity in a material-sparing and expedited manner. [Display omitted]